Characterization of silica-carbon mesoporous matrix with embedded nickel nanoparticles synthesized by the polymeric precursor method - Cavalheiro, A. A.; Bruno, J. C.; Leite, E. R.; Varela, José Arana [UNESP] (Elsevier B.V., 2007)
Nickel nanoparticles into silica-carbon matrix composites were prepared by using the polymeric precursor method. The effects of the polyester type and the time of pyrolysis on the mesoporosity and nickel particle dispersion into non-aqueous amorphous silica-carbon matrix were investigated by thermogravimetric analysis, adsorption/desorption isotherms and TEM. A well-dispersed metallic phase could be only obtained by using ethylene glycol. Weightier polyesters affected the pyrolysis process due to a combination of more amounts of carbonaceous residues and delaying of pyrolysis process. The post-pyrolyzed composites were successfully cleaned at 200 degrees C for I h in oxygen atmosphere leading to an increase in the surface area and without the occurrence of carbon combustion or nickel nanoparticles oxidation. The matrix composites presented predominantly mesoporous with pore size well defined in 38 angstrom, mainly when tetraethylene glycol was used as polymerizing agent. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: composite materials; chemical synthesis; thermogravimetric analysis